Model of Grid-Connected PV System in Sarawak, Malaysia Rural Area - Yanuar Z., Arief; Sebastian Sulau, Sa-Or; Naemah, Mubarakah; Mohd Hafiez Izzwan, Saad; Hamzah, Eteruddin (IEEE, 2020)
Sarawak is largest states in Malaysia and is gifted with lush forest and hilly terrains. However, due to this topography, Sarawak Energy Berhad (SEB) has difficulty to supply a reliable source of electricity to all areas of Sarawak. There are even areas with grid connection that occasionally suffer from power outage. Solar energy can be seen as a solution to the problem of supplying reliable power. However, installing and operating a PV system to generate power will require some insight on the location and the technical information of the PV system. Therefore, this paper aims to collect and analyze the resource data of the locations in Sarawak as well as the possible characteristics of a grid-connected PV system. The project starts with the possible locations of the PV system. The locations include area throughout Sarawak such as Sri Aman, Kapit, Limbang, Lundu, Sebuyau, Tatau and Lawas, respectively. The resource data of the area such as the average annual irradiance and the average annual ambient temperature is collected through HOMER software. The components used to test the characteristics of the PV system are CanadianSolar KuBlack C32K 300MS solar panel, Mitsubishi Electric PV-MLU250HC solar panel, Canadian Solar Single Phase String Inverter CSI-2KTL1P-GI-FL and Mitsubishi Electric Photovoltaic Inverter PVS2600, respectively. Then, the components will interchange into a combination of one PV module and one inverter to make four different sets of PV system. The result of the project revealed that the area of Limbang and Lawas is the most suitable for a Grid connected PV system because the two areas have high irradiance and low ambient temperature. The most suitable combination of components is the Mitsubishi Electric PV-MLU250HC solar panel and CanadianSolar Single Phase String Inverter CSI-2KTL1P-GIFL. This combination component has the least loss which means the PV system is efficient.